Integrating Corpus Linguistics to Enhance English Language Proficiency Among Elementary School Teachers - Lestariningsih, Fransisca Endang; Subekti, Adaninggar Septi; Kurniawati, Lemmuela Alvita (Journal of Languages and Language Teaching, 2025)
Corpus linguistics is widely recognized as a branch of linguistics that analyzes and derives insights from authentic language usage, as it emphasizes on the use of large electronic collections of texts referred to as corpora to analyses real-world language use. The rise of corpus linguistics has closely followed advancements in computer storage capacity and processing speed. This study seeks to develop a nationwide English language training program for elementary school teachers. In the initial stage, training modules was designed for these teachers. The research employed the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate), utilizing interviews and questionnaires as data collection instruments, followed by the implementation of the training modules through direct instruction. The participants of this study were 19 elementary school teachers. The findings indicate that incorporating corpus linguistics into the training significantly reduced teachers' anxiety, enhanced their fluency, and improved their overall competency. Â Future research should explore strategies to better support teachersâ€™ professional language development and enhance English instruction in elementary schools.